First record of the smallest extant brachiopod Gwynia capsula (Jeffreys, 1859) from the German Bight - Carsten Lüter; Anke Sänger; Fabia Wagner (PLoS ONE, 2026)
We describe for the first time the occurrence of the smallest extant brachiopod, Gwynia capsula (Jeffreys, 1859), from the island of Helgoland. A single living specimen was found in dredged shell gravel from the Helgoland trench (“Tiefe Rinne”) mainly consisting of large dead shells of the bivalves Ostrea edulis and Modiolus modiolus . G. capsula was identified through its minute size and its characteristic submarginal ridges on the inside of the dorsal valve supporting the trocholophous lophophore of the animal. Among other localities, populations of G. capsula are known from British waters as well as the continental coasts of, e.g., France, Belgium and the Netherlands. However, the reproductive biology of the species makes it rather unlikely that larvae of G. capsula have reached Helgoland by natural drift. It is briefly discussed whether ship-based trading throughout the 19 th century may have had an influence here.